Comparison Between Recovery Profiles of Total Propofol Anesthesia and Total Sevoflurane Anesthesia in Patients Undergoing Laparoscopic Cholecystectomy - Anum Sultan, Hamza Bin Ali, Samina Ashraf, Kiran Riaz Khan, Hana Khurshid, Ali Kashif, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To compare propofol and sevoflurane anesthesia in terms of mean extubation time among patients undergoing laparoscopic cholecystectomy. Study Design: Randomized Controlled Trial Study Setting: National Hospital and Medical Centre, Lahore Sampling Technique: Consecutive non-probability sampling Study duration: 06-02-18 to 06-08-18 Methodology: The cases with age range of 16 to 60 years of either gender with ASA status 1 and 2 undergoing laparoscopic cholecystectomy were included. group A was given propofol and group B sevoflurane in standard dose and they were assessed for mean extubation time. Results: In the present study there were total 60 cases with 30 in each group. There were 14 (46.67%) males in group A vs 16 (53.33%) in group B. The mean age in the group A was 40.03±13.68 years while in group B was 36.83±10.64 years. Mean BMI was 25.27±2.05 vs 25.43±1.85 in group A and B respectively. There were 19 (63.33%) cases in ASA class 1 in group A and 16 (53.33%) in group B. Mean extubation time in group A and B was 7.16±2.80 vs 3.68±0.87 with p= 0.0001. Mean time of extubation was significantly longer in group A in terms of gender, age and ASA class. Conclusion: Mean extubation time was significantly shorter in group B managed by Sevoflurane as compared to Propofol and this difference was statistically significant in terms of all the variables in the form of age, gender and ASA class. Thus sevolflurane anaesthesia is superior to propofol. Keywords: Anesthesia, Sevoflurane, Propofol, Extubation Time, ASA Status.